Numerical model for small-signal modulation response in vertical-cavity surface-emitting lasers. (8th June 2020) - Wasiak, Michał; Śpiewak, Patrycja; Haghighi, Nasibeh; Gȩbski, Marcin; Pruszyńska-Karbownik, Emilia; Komar, Paulina; Lott, James A; Sarzała, Robert P
Abstract: We present a numerical model allowing for simulations of small-signal modulation (SSM) response of vertical-cavity surface-emitting lasers (VCSELs). The model of SSM response utilizes only the data provided by a static model of continuous-wave operation for a given bias voltage. Thus the fitting of dynamic measurement parameters is not needed nor used. The validity of this model has been verified by comparing experimental SSM characteristics of a VCSEL with the results of simulations. A good agreement between experiment and simulations has been observed. Based on the results obtained in the simulations of the existing laser, the impact of the number of quantum wells in the active region on the modulation properties has been calculated and analyzed.